Reclamation of Ravines of Chambal Commanded Area - Seth, S. P.; Bhatnagar, R. K.; Chouhan, S. S. (Indian Forester, 1970)
About sixteen handred hectares of ravinous area in Chambal Commanded area was surveyed and classified into eight reclaimability classes as suggested by the Committee on Natural Resources Planning Commission (1965). 38.7 per cent of the ravines can be put for agriculture and horticulture purpose while the rest of the area can be used for grass-land and forestry.